Involved Site Radiotherapy Extends Time to Premature Menopause in Infra-Diaphragmatic Female Hodgkin Lymphoma Patients – An Analysis of GHSG HD14- and HD17-Patients - Rosenbrock, Johannes; Vásquez-Torres, Andrés; Mueller, Horst; Behringer, Karolin; Zerth, Matthias; Celik, Eren; Fan, Jiaqi; Trommer, Maike; Linde, Philipp; Fuchs, Michael; Borchmann, Peter; Engert, Andreas; et al. (Frontiers in Oncology, 2021)
Introduction: Consolidation radiotherapy in intermediate stage Hodgkin´s lymphoma (HL) has been the standard of care for many years as involved field radiotherapy (IFRT) after chemotherapy. It included initially involved region(s). Based on randomized studies, radiation volumes could be reduced and involved site radiation therapy (ISRT) became the new standard. ISRT includes the initially affected lymph nodes. In young adults suffering from HL, infertility and hypogonadism are major concerns. With regard to these questions, we analyzed the influence of modern radiotherapy concepts such as consolidating ISRT in infradiaphragmatic involvement of HL after polychemotherapy. Patients and methods: Five hundred twelve patients treated within German Hodgkin Study Group (GHSG) HD14 and HD17 trials were evaluated. We analyzed log-adjusted follicle-stimulating-hormone (FSH)- and luteinizing-hormone (LH)-levels of HD14-patients with infradiaphragmatic radiotherapy (IDRT) in comparison with HD14-patients, who had a supradiaphragmatic radiotherapy (SDRT). In a second step, we compared IFRT with ISRT of female HD17 patients regarding the effects on ovarian function and premature menopause. Results: We analyzed FSH- and LH-levels of 258 female and 241 male patients, all treated with IFRT. Of these 499 patients, 478 patients had SDRT and 21 patients had IDRT. In a multiple regression model, we could show that log-adjusted FSH (p=0.0006) and LH values (p=0.0127) were significantly higher after IDRT than after SDRT. The effect of IDRT on gonadal function was comparable to two cycles of escalated bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone (BEACOPPesc). We compared the effect of IFRT with ISRT in thirteen female HD17 patients with infra-diaphragmatic (ID) involvement. The mean ovarian dose after ISRT was significantly lower than after IFRT. The calculated proportion of surviving non-growing follicles (NGFs) increased significantly from 11.87% to 24.48% in ISRT compared to IFRT, resulting in a significantly longer calculated time to menopause. The younger the age at therapy, the greater the absolute time gain until menopause. Conclusion: Infradiaphragmatic IFRT impairs gonadal function to a similar extent as two cycles of BEACOPPesc. In comparison, the use of ISRT target volume definition significantly reduced radiation dose to the ovaries and significantly extends the time interval from treatment to premature menopause.